Global companies and its impact on GDP and workforce (socio-economic structure) of China - Yun, Han (2019)
With the deepening of economic globalization, multinational corporations have become an important force in promoting the development of the world economy. Since China entered WTO, the multinational corporations (MNC) increased the foreign direct investment (FDI) in Chinese market because China is famous for its huge market volume and low labor cost. However, the knowledge of Chinese marketis still limited. Fundamentally speaking, the impact of multinational corporations’ investment in China on China is mainly reflected in the economy. At the same time, it is a double-edged sword. The impact on the economy is divided into positive and negative aspects. We should correctly position multinational corporations and their economic impact.